1994
DOI: 10.1111/j.1398-9995.1994.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in steroid‐dependent asthma: long‐term results

Abstract: Treatment of 21 steroid-dependent asthmatic patients with methotrexate (MTX) 15 mg/week was prospectively evaluated for a mean of 14.7 (SD 3.7) months. Before MTX, therapy consisted of a mean prednisone dose of 16.6 (SD 9.2) mg, in addition to inhaled beclomethasone/budesonide (mean daily dose 1157 (SD 330) micrograms) and bronchodilators. Thirteen patients were weaned from all regular systemic steroid therapy, a 50% or more reduction was achieved in four patients, and a less than 50% reduction in four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, in asthma adenosine is a potent bronchoconstrictor probably due to activation of mast cells via A2-receptors [35]. In clinical trials conducted so far [11], the absence of reduced, and incidentally even increased, bronchial hyperresponsiveness following MTX treatment might be associated with increased release of adenosine, and explain the clinical deterioration observed in this patient. This raises the possibility that the final outcome of MTX treatment in glucocorticoid-dependent asthmatics, therefore, may depend on the balance between improved responsiveness to the suppressive action of glucocorticoids and the degree of MTX-induced autocoid release.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in asthma adenosine is a potent bronchoconstrictor probably due to activation of mast cells via A2-receptors [35]. In clinical trials conducted so far [11], the absence of reduced, and incidentally even increased, bronchial hyperresponsiveness following MTX treatment might be associated with increased release of adenosine, and explain the clinical deterioration observed in this patient. This raises the possibility that the final outcome of MTX treatment in glucocorticoid-dependent asthmatics, therefore, may depend on the balance between improved responsiveness to the suppressive action of glucocorticoids and the degree of MTX-induced autocoid release.…”
Section: Discussionmentioning
confidence: 80%
“…A number of open studies has suggested clinical efficacy of MTX [10,11]. This has been confirmed in doubleblind placebo-controlled trials [12,13].…”
Section: Discussionmentioning
confidence: 82%
“…When steroids cannot be withdrawn or do not induce remission in both asthma and IBD, antimetabolites or immunosuppressive agents such as methotrexate (128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143) and azathioprine/6-mercaptopurine (6-MP) (144) are used. Methotrexate may have an important inhibitory effect on cytokine synthesis and activity.…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%
“…[21] 21 patients corticosteroiddependent asthma were treated with methotrexate IS mg/ week over a mean period of 14.3 months. 13 of the 21 patients were completely weaned from all regular systemic corticosteroid therapy and a greater than 50% reduction in systemic corticosteroid dosage was noted in another 4 patients.…”
Section: Adultsmentioning
confidence: 99%